Una visión crítica del Artículo 49 del E.T.N. (2018)
The Colombian legislation has the possibility of using the excess of dividends not taxed in a period to distribute profits that in principle are considered as taxed from other periods. However, is it possible to consider that this norm that made it possible to compensate for excess profits not taxed in future periods and even with previous profits is sufficient?